Sharp Periodic Flares and Long-term Variability in the High-mass X-Ray Binary XTE J1829−098 from RXTE PCA, Swift BAT, and MAXI Observations - Corbet, Robin H.D.; Ballhausen, Ralf; Becker, Peter A.; Coley, Joel B.; Fuerst, Felix; Gendreau, Keith C.; Guillot, Sebastien; Islam, Nazma; Jaisawal, Gaurava Kumar; Jenke, Peter; Kretschmar, Peter; Lange, Alexander; et al. (Astrophysical Journal, 2024)
XTE J1829−098 is a transient X-ray pulsar with a period of ∼7.8 s. It is a candidate Be star system, although the evidence for this is not yet definitive. We investigated the twenty-year-long X-ray light curve using the Rossi X-ray Timing Explorer Proportional Counter Array (PCA), Neil Gehrels Swift Observatory Burst Alert Telescope, and the Monitor of All-sky X-ray Image. We find that all three light curves are clearly modulated on the ∼244 days orbital period previously reported from PCA monitoring observations, with outbursts confined to a narrow phase range. The light curves also show that XTE J1829−098 was in an inactive state between approximately 2008 December and 2018 April, and no strong outbursts occurred. Such behavior is typical of Be X-ray binary systems, with the absence of outbursts likely related to the dissipation of the Be star's decretion disk. The mean outburst shapes can be approximated with a triangular profile and, from a joint fit of this to all three light curves, we refine the orbital period to 243.95 ± 0.04 days. The mean outburst profile does not show any asymmetry and has a total phase duration of 0.140 ± 0.007. However, the PCA light curve shows that there is considerable cycle-to-cycle variability of the individual outbursts. We compare the properties of XTE J1829−098 with other sources that show short phase-duration outbursts, in particular GS 1843−02 (2S 1845−024), which has a very similar orbital period, but longer pulse period, and whose orbit is known to be highly eccentric.
CRIS-Team Scopus Importer:2024-12-13